Tackifying type cave slag stone powder-based composite mineral admixture as well as preparation method and application of tackifying type cave slag stone powder-based composite mineral admixture

By using a viscosity-enhancing hole slag stone powder-based composite mineral blend, the problem of improving concrete viscosity in the prior art is solved, good thixotropic performance and shape retention ability in the jet construction environment is achieved, and the treatment cost of hole slag stone powder is reduced.

CN119797792APending Publication Date: 2025-04-11MCC COMM CONSTR GRP CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411788203.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the viscosity of concrete, especially in the spray construction environment, and the traditional viscosity-enhancing admixtures have complex processes, high costs and unclear mechanisms, which can easily affect the durability of concrete.

Method used

The viscosity-enhancing hole-slag stone powder-based composite mineral blend is used, which includes hole-slag stone powder, lubricated water-retaining materials, clay mineral materials and silicon calcium materials. It is prepared through grinding and mixing processes to improve the rheological performance of concrete.

Benefits of technology

It significantly improves the viscosity of concrete, enhances its thixotropic performance and shape retention ability in jet construction, reduces the losses caused by material rebound during construction, and realizes the resource utilization of hole slag and stone powder, reducing treatment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of building materials, in particular to a tackifying type cave slag stone powder-based composite mineral admixture as well as a preparation method and application thereof. The tackifying type cave slag stone powder-based composite mineral admixture is prepared from the following components in parts by weight: 70 to 90 parts of cave slag stone powder, 2 to 5 parts of lubricating and water-retaining materials, 8 to 16 parts of clay mineral materials and 40 to 45 parts of silicon-calcium materials. The tackifying type cave slag stone powder-based composite mineral admixture can improve the rheological property of concrete, so that the concrete has good thixotropic property and shape retention capability during spraying construction, the loss caused by material resilience in the construction process is reduced, meanwhile, resource utilization of cave slag stone powder can be realized, and the resource utilization rate of the cave slag stone powder is increased. And the product additional value of hole slag solid waste recycling is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building materials, in particular to a viscosity-enhancing slag stone powder-based composite mineral admixture and a preparation method and application thereof. Background Art

[0002] Mineral admixtures are an indispensable component of modern concrete. After being mixed with cement, sand, stone, water, and admixtures in specific proportions, concrete is formed through the stages of mixing, pouring, curing, and hardening. The role of mineral admixtures in concrete can be categorized into three effects: the pozzolanic effect, the microaggregate effect, and the morphological effect. The pozzolanic effect refers to the active silica (SiO2) and alumina (Al2O3) contained in mineral admixtures. These components, stimulated by the alkaline hydration product Ca(OH)2 of cement, undergo a secondary hydration reaction to form hydraulically hardening substances such as calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH). These substances fill the capillary pores and enhance the strength of concrete. The microaggregate effect refers to the uniform distribution of fine particles in the mineral admixture within the cement paste matrix. Like fine aggregate, they fill the gaps between sand and cement particles, making the concrete mortar system more compact. The morphological effect refers to the smooth particles such as some glass beads contained in the mineral admixture. These particles make the particles in the cement paste evenly dispersed, reduce the friction between the particles, and make the paste more fluid.

[0003] The development of mineral admixtures has gone through several stages. The first stage was the stage of single, traditional material types such as fly ash and mineral powder. The second stage was the stage of single, new materials such as various metallurgical solid waste micropowders (steel slag powder, gold / tungsten / copper tailings powder) and rock micropowders of different lithologies (limestone, granite, gneiss). The third stage, which is also the current stage, has seen mineral admixtures gradually move from a variety of new single materials to composite materials, that is, new, composite materials formed by mixing two or more of the above materials. In particular, as large-scale infrastructure projects using concrete are shifting to the mountainous and plateau regions of southwestern my country, traditional mineral admixtures such as fly ash and mineral powder are becoming increasingly difficult to obtain. However, the slag generated during tunnel excavation in mountainous areas can be used to prepare rock powder, which in turn is a suitable raw material for preparing new composite mineral admixtures.

[0004] The properties of mineral admixtures significantly impact the performance of concrete, influencing its overall properties to varying degrees through their three main effects. One such property relates to concrete's viscosity. For example, concrete used in shotcrete construction requires a high viscosity to minimize rebound and dispersion during spraying, reducing construction waste and lowering construction costs. Therefore, enhancing concrete viscosity is a technical requirement for specialized construction environments like shotcrete.

[0005] The current method of increasing concrete viscosity is through the use of chemical polymer admixtures, but there are several problems. First, the preparation and synthesis process is complex and costly. Second, the unclear viscosity-increasing mechanism leads to poor adaptability to different materials. Third, it can easily lead to problems with concrete durability, which is not worth the cost. Existing technologies often cannot effectively balance these multiple properties and may even cause conflicts. For example, cellulose ether materials commonly used in concrete can improve the viscosity of concrete before hardening, but they can significantly affect the mechanical properties of the hardened mortar, weakening the strength of the cement interface transition zone, resulting in reduced concrete flexural strength, compressive strength, and bond tensile strength. The greater the addition amount, the greater the reduction.

[0006] The resource utilization of tunnel slag is of great significance for optimizing costs, improving efficiency, and protecting the environment. Existing technologies mostly crush tunnel slag into machine-made sand and gravel for use, but the technology of using tunnel slag to prepare composite mineral admixtures is relatively rare.

[0007] In view of this, the present invention is proposed. Summary of the Invention

[0008] The purpose of the present invention is to provide a viscosity-enhancing slag stone powder-based composite mineral admixture, a preparation method and application thereof. The viscosity-enhancing slag stone powder-based composite mineral admixture can improve the rheological properties of concrete, so that the concrete has good thixotropic properties and shape retention ability during spraying construction, and reduce the loss caused by material rebound during the construction process.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted:

[0010] One aspect of the present invention relates to a tackifying type slag stone powder-based composite mineral admixture, comprising the following components in parts by weight:

[0011] 70-90 parts of slag stone powder, 2-5 parts of lubricating and water-retaining materials, 8-16 parts of clay mineral materials and 40-45 parts of silicon-calcium materials.

[0012] The viscosity-enhancing slag stone powder-based composite mineral admixture can improve the rheological properties of concrete, so that the concrete has good thixotropic properties and shape retention ability during spraying construction, reduce the loss caused by material rebound during the construction process, realize resource utilization of slag stone powder, and reduce the processing cost of slag stone powder.

[0013] Preferably, the viscosity-enhancing slag stone powder-based composite mineral admixture comprises the following components in parts by weight:

[0014] 75-85 parts of slag stone powder, 3-4 parts of lubricating and water-retaining materials, 9-15 parts of clay mineral materials and 42-44 parts of silicon-calcium materials.

[0015] Preferably, the fineness of the slag stone powder is ≥300 mesh, the moisture content is below 1%, and the 45 micron sieve residue is ≤10%.

[0016] Preferably, the lithology of the cave slag powder includes at least one of gneiss, sandstone, clastic rock, slate, phyllite, granite-type igneous rock and volcanic rock.

[0017] Preferably, the rock-forming mineral composition of the slag powder includes at least one of calcite, quartz, feldspar or dolomite.

[0018] Preferably, the lubricating and water-retaining material includes: magnesium aluminum silicate and / or bentonite.

[0019] Preferably, the clay mineral material includes at least one of diatomaceous earth, montmorillonite or metakaolin.

[0020] Preferably, the calcium-silicon material includes at least one of silica fume, glass beads or ultrafine mineral powder.

[0021] Another aspect of the present invention also relates to a method for preparing the viscosity-enhancing slag stone powder-based composite mineral admixture, comprising the following steps:

[0022] After the slag rock is crushed, it enters the mill and is ground to the specified fineness. Then various functional components are added according to the proportion and put into the mixer to mix the components evenly.

[0023] The preparation method of the viscosity-enhancing slag stone powder-based composite mineral admixture is simple, easy to operate, does not require reliance on complex process equipment, and has low preparation cost.

[0024] Another aspect of the present invention also relates to a concrete, comprising the viscosity-enhancing slag powder-based composite mineral admixture described above or the viscosity-enhancing slag powder-based composite mineral admixture prepared by the preparation method of the viscosity-enhancing slag powder-based composite mineral admixture described above.

[0025] The concrete has good rheological properties, thixotropic properties and shape retention ability. It does not block the pipe during pumping to ensure continuous construction. It is easy to atomize and does not form lumps to ensure density without voids. It is easy to thixotropic and does not sag to reduce material rebound loss.

[0026] Preferably, the addition amount of the viscosity-enhancing slag stone powder-based composite mineral admixture is 5% to 30% of the total mass of the cementitious material of the concrete.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The viscosity-enhancing slag stone powder-based composite mineral admixture provided by the present invention mainly includes slag stone powder as the main raw material, which can realize the resource utilization of slag stone powder and reduce the processing cost of slag stone powder; it is compounded with an appropriate amount of water-retaining lubricant, clay minerals and silica-calcium materials. The synergistic effect of each component can improve the rheological properties of concrete, so that the concrete has good thixotropic properties and shape retention ability during spraying construction, reduces the loss caused by material rebound during the construction process, and significantly improves the viscosity of the concrete.

[0029] (2) The preparation method of the thickening type slag stone powder-based composite mineral admixture provided by the present invention is simple and easy to operate, does not rely on complex process equipment, and has low preparation cost. The prepared thickening type slag stone powder-based composite mineral admixture has excellent performance and can improve the performance of concrete when added to concrete.

[0030] (3) The concrete provided by the present invention is added with a viscosity-enhancing slag stone powder-based composite mineral admixture, which has good rheological properties, thixotropic properties and shape retention ability. The pumping process does not block the pipe to ensure continuous construction. It is easy to atomize and does not form lumps to ensure density without voids. It is easy to thixotropic and does not sag to reduce material rebound loss, and the viscosity of the concrete is significantly improved. DETAILED DESCRIPTION

[0031] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to normal conditions or the conditions recommended by the manufacturer. Those whose reagents or instruments are not specified by the manufacturer are conventional products that can be purchased commercially.

[0032] One aspect of the present invention relates to a tackifying type slag stone powder-based composite mineral admixture, comprising the following components in parts by weight:

[0033] 70-90 parts of slag stone powder, 2-5 parts of lubricating and water-retaining materials, 8-16 parts of clay mineral materials and 40-45 parts of silicon-calcium materials.

[0034] In some specific embodiments, the slag stone powder can be, for example, but not limited to, any one of 70 parts, 73 parts, 75 parts, 78 parts, 80 parts, 83 parts, 85 parts, 88 parts or 90 parts by weight, or a range value between any two parts.

[0035] In some specific embodiments, the amount of the lubricating and water-retaining material can be, for example, but not limited to, 2 parts, 3 parts, 4 parts, or 5 parts, or a range of values ​​between any two parts, by weight.

[0036] In some specific embodiments, the clay mineral material can be, for example, but not limited to, any one of 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts or 16 parts by weight, or a range between any two of them.

[0037] In some specific embodiments, the amount of the silicon-calcium material can be, for example, but not limited to, any one of 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, or 45 parts by weight, or a range of values ​​between any two of them.

[0038] In response to the problems of high cost of treating tunnel slag generated during infrastructure construction, low resource utilization, and potential risks of existing treatment technologies, the present invention designs a method for utilizing tunnel slag solid waste resources with high added value and high resource utilization rate. That is, stone powder is produced from tunnel slag, which is compounded with other materials as a functional composite mineral admixture to prepare concrete, significantly improving the viscosity of the concrete.

[0039] The viscosity-enhancing slag stone powder-based composite mineral admixture mainly includes slag stone powder as its main raw material, which can realize the resource utilization of slag stone powder and reduce the processing cost of slag stone powder; it is compounded with appropriate amounts of lubricants, fillers, clay minerals and siliceous materials. The synergistic effect of each component can improve the rheological properties of concrete, so that the concrete has good thixotropic properties and shape retention ability during spraying construction, reduces the loss caused by material rebound during the construction process, and significantly improves the viscosity of the concrete.

[0040] Furthermore, the viscosity-enhancing slag stone powder-based composite mineral admixture comprises the following components in parts by weight:

[0041] 75-85 parts of slag stone powder, 3-4 parts of lubricating and water-retaining materials, 9-15 parts of clay mineral materials and 42-44 parts of silicon-calcium materials.

[0042] Furthermore, the fineness of the slag stone powder is ≥300 mesh, the moisture content is below 1%, and the 45 micron sieve residue is ≤10%.

[0043] Furthermore, the lithology of the cave slag powder includes but is not limited to at least one of gneiss, sandstone, clastic rock, slate, phyllite, granite-type igneous rock and volcanic rock.

[0044] The tunnel slag stone powder mentioned in the present invention is a fine powder obtained by removing mud, drying and grinding the stone produced during the tunnel excavation process.

[0045] Furthermore, the lubricating and water-retaining materials include but are not limited to magnesium aluminum silicate and / or bentonite. The lubricating and water-retaining materials work synergistically with other components to improve the working performance and durability of concrete, and are beneficial to improving the viscosity of concrete.

[0046] Furthermore, the clay mineral material includes but is not limited to at least one of diatomaceous earth, montmorillonite or metakaolin. Clay mineral materials can synergistically act with other components to improve the strength and stability of concrete and also enhance the impermeability of concrete.

[0047] Furthermore, the calcium-silicon material includes but is not limited to at least one of silica fume, glass beads or ultrafine mineral powder. The calcium-silicon material works synergistically with other components to increase the strength of concrete and improve the fluidity of concrete.

[0048] Another aspect of the present invention also relates to a method for preparing the viscosity-enhancing slag stone powder-based composite mineral admixture, comprising the following steps:

[0049] After the slag rock is crushed, it enters the mill and is ground to the specified fineness. Then various functional components are added according to the proportion and put into the mixer to mix the components evenly.

[0050] The preparation method of the viscosity-enhancing slag stone powder-based composite mineral admixture is simple and easy to operate, does not rely on complex process equipment, and has low preparation cost. The prepared viscosity-enhancing slag stone powder-based composite mineral admixture has excellent performance and can improve the performance of concrete when added to concrete.

[0051] Another aspect of the present invention also relates to a concrete, comprising the viscosity-enhancing slag powder-based composite mineral admixture described above or the viscosity-enhancing slag powder-based composite mineral admixture prepared by the preparation method of the viscosity-enhancing slag powder-based composite mineral admixture described above.

[0052] The concrete is added with a certain amount of viscosity-enhancing slag stone powder-based composite mineral admixture, has good rheological properties, thixotropic properties and shape retention ability, does not block the pipe during pumping to ensure continuous construction, is easy to atomize and does not form lumps to ensure density without voids, is easy to thixotropic and does not sag to reduce material rebound loss, and the viscosity of the concrete is significantly improved.

[0053] Furthermore, the addition amount of the viscosity-enhancing slag stone powder-based composite mineral admixture is 5% to 30% of the total mass of the cementitious material of the concrete, including but not limited to any one of 5%, 10%, 15%, 20%, 25% or 30% or the range value between any two of them.

[0054] The viscosity-enhancing slag stone powder-based composite mineral admixture provided by the present invention only needs to be added in an amount of 5% to 30% to the concrete cementitious material to improve the performance of the concrete. The small amount of addition will not increase the preparation cost of the concrete.

[0055] The embodiments of the present invention will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present invention and should not be construed as limiting the scope of the invention. Where specific conditions are not specified in the examples, the methods were performed according to conventional conditions or the conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments are not specified, they are all commercially available conventional products.

[0056] Example 1

[0057] The viscosity-enhancing slag stone powder-based composite mineral admixture provided in this embodiment includes the following components in parts by weight:

[0058] 70 parts of slag stone powder, 5 parts of lubricating and water-retaining materials, 8 parts of clay mineral materials and 45 parts of silicon-calcium materials;

[0059] Among them, the lubricating and water-retaining material is magnesium aluminum silicate, the clay mineral material is 5 parts of diatomaceous earth and 3 parts of montmorillonite, and the calcium silicon material is silica fume.

[0060] Example 2

[0061] The viscosity-enhancing slag stone powder-based composite mineral admixture provided in this embodiment includes the following components in parts by weight:

[0062] 90 parts of slag stone powder, 2 parts of lubricating and water-retaining materials, 16 parts of clay mineral materials and 40 parts of silicon-calcium materials;

[0063] Among them, the lubricating and water-retaining material is bentonite, the clay mineral material is montmorillonite, and the silicon-calcium material is silica fume.

[0064] Example 3

[0065] The viscosity-enhancing slag stone powder-based composite mineral admixture provided in this embodiment includes the following components in parts by weight:

[0066] 85 parts of slag stone powder, 4 parts of lubricating and water-retaining materials, 9 parts of clay mineral materials and 42 parts of silicon-calcium materials;

[0067] Among them, the lubricating and water-retaining material is magnesium aluminum silicate, the clay mineral material is diatomaceous earth, and the calcium silicon material is glass microspheres.

[0068] Example 4

[0069] The viscosity-enhancing slag stone powder-based composite mineral admixture provided in this embodiment includes the following components in parts by weight:

[0070] 75 parts of slag stone powder, 3 parts of lubricating and water-retaining materials, 15 parts of clay mineral materials and 44 parts of silicon-calcium materials;

[0071] Among them, the lubricating and water-retaining material is bentonite, the clay mineral material is metakaolin, and the silicon-calcium material is ultrafine mineral powder.

[0072] Example 5

[0073] The viscosity-enhancing slag stone powder-based composite mineral admixture provided in this comparative example comprises the following components in parts by weight:

[0074] 80 parts of slag stone powder, 3.5 parts of lubricating and water-retaining materials, 10 parts of clay mineral materials and 43 parts of silicon-calcium materials;

[0075] Among them, the lubricating and water-retaining material is magnesium aluminum silicate, the clay mineral material is 6 parts of diatomaceous earth and 4 parts of montmorillonite, and the calcium silicon material is silica fume.

[0076] Comparative Example 1

[0077] The only difference between this comparative example and Example 5 is that no lubricating and water-retaining material is added.

[0078] Comparative Example 2

[0079] The only difference between this comparative example and Example 5 is that no clay mineral material is added.

[0080] Comparative Example 3

[0081] The only difference between this comparative example and Example 5 is that no silicon-calcium material is added.

[0082] Experimental example

[0083] The viscosity-enhancing slag stone powder-based composite mineral admixture provided in each embodiment and comparative example was added to the concrete according to the formula provided by the experimental group in Table 1, and the performance of the concrete was tested. The test results are shown in Table 2.

[0084] Table 1 Shotcrete test group settings and formulation composition

[0085]

[0086] Table 2 Comparison of shotcrete performance indicators

[0087]

[0088]

[0089] From the comparative data in Table 2, it can be seen that compared with the blank group, after using the viscosity-enhancing slag stone powder-based composite mineral admixture of the present invention, the rheological construction performance of the concrete before hardening and the bonding strength performance of the concrete after hardening can be significantly improved.

[0090] Compared to conventional viscosity-enhancing admixture additions, the use of the present invention's viscosity-enhancing slag powder-based composite mineral admixture maintains similar rheological properties before hardening, while outperforming the conventional additions of viscosity-enhancing admixtures in terms of pumpability. Furthermore, the adhesive strength performance of the mortar after hardening is significantly superior to that of the conventional additions of viscosity-enhancing admixtures, avoiding the strength degradation associated with the use of viscosity-enhancing admixtures, improving workability, and ensuring the reinforcement effect.

[0091] Although the present invention has been illustrated and described using specific embodiments, it should be appreciated that the above embodiments are merely intended to illustrate the technical solutions of the present invention rather than to limit them. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and scope of the present invention. However, these modifications or replacements do not deviate from the essence of the corresponding technical solutions within the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A viscosity-enhancing slag stone powder-based composite mineral admixture, characterized in that: By weight, it includes the following components: 70-90 parts of slag stone powder, 2-5 parts of lubricating and water-retaining materials, 8-16 parts of clay mineral materials and 40-45 parts of silicon-calcium materials.

2. The viscosity-enhancing slag stone powder-based composite mineral admixture according to claim 1, characterized in that: By weight, it includes the following components: 75-85 parts of slag stone powder, 3-4 parts of lubricating and water-retaining materials, 9-15 parts of clay mineral materials and 42-44 parts of silicon-calcium materials.

3. The viscosity-enhancing slag stone powder-based composite mineral admixture according to claim 1 or 2, characterized in that: The slag powder has a fineness of ≥300 meshes, a moisture content of less than 1%, and a 45-micron sieve residue of ≤10%.

4. The viscosity-enhancing slag stone powder-based composite mineral admixture according to claim 1 or 2, characterized in that: The lithology of the cave slag powder includes at least one of gneiss, sandstone, clastic rock, slate, phyllite, granite igneous rock and volcanic rock.

5. The viscosity-enhancing slag stone powder-based composite mineral admixture according to claim 1 or 2, characterized in that: The lubricating and water-retaining materials include: magnesium aluminum silicate and / or bentonite.

6. The viscosity-enhancing slag stone powder-based composite mineral admixture according to claim 1 or 2, characterized in that: The clay mineral material includes at least one of diatomaceous earth, montmorillonite or metakaolin.

7. The viscosity-enhancing slag stone powder-based composite mineral admixture according to claim 1 or 2, characterized in that: The calcium-silicon material includes at least one of silica fume, glass beads or ultrafine mineral powder.

8. The method for preparing the viscosity-enhancing slag stone powder-based composite mineral admixture according to any one of claims 1 to 7, characterized in that: The following steps are involved: After the slag rock is crushed, it enters the mill and is ground to the specified fineness. Then various functional components are added according to the proportion and put into the mixer to mix the components evenly.

9. A concrete, characterized in that: The invention relates to a viscosity-enhancing slag powder-based composite mineral admixture prepared by the viscosity-enhancing slag powder-based composite mineral admixture described in any one of claims 1 to 7 or the viscosity-enhancing slag powder-based composite mineral admixture described in claim 8.

10. The concrete according to claim 9, characterized in that The added amount of the viscosity-enhancing slag stone powder-based composite mineral admixture is 5% to 30% of the total mass of the cementitious material of the concrete.